Evaluation of Coronavirus Disease 2019 Burnout Syndrome Among Healthcare Workers in Taizhou, China - Tao-Hsin Tung; Yu-Pei Yang; Mei-Xian Zhang; Hai-Xiao Chen; Shuang-Jun Pan (Frontiers Media S.A., 2023)
Objectives: To evaluate COVID-19 burnout syndrome among healthcare workers in Taizhou, China.Methods: A total of 1,103 qualified healthcare workers in Taizhou were included in the study. The Maslach Burnout Inventory-General Survey (MBI-GS) was used to assess burnout syndrome.Results: Among the healthcare workers surveyed, 25.9% experienced COVID-19 burnout syndrome, including 22.3% and 3.6% with mild and moderate burnout, respectively. Multivariate linear regression models revealed associations with emotional exhaustion among healthcare workers, as follows: occupation, education level and professional qualifications. Professional efficacy was impacted by the pandemic, as follows: sex and occupation. The following factors were associated with cynicism among healthcare workers: occupation and underlying disease. Occupation (medical technician vs. physician, β = −7.40, 95% confidence interval: −12.09 to −2.71, p = 0.002) was significantly related to MBI-GS scores after adjusting for confounding factors.Conclusion: COVID-19 burnout syndrome was common among healthcare workers in Taizhou, China, and its impact was more burdensome to physicians.